2023
DOI: 10.1042/bcj20220220
|View full text |Cite
|
Sign up to set email alerts
|

Principles of phosphoproteomics and applications in cancer research

Abstract: Phosphorylation constitutes the most common and best-studied regulatory post-translational modification in biological systems and archetypal signalling pathways driven by protein and lipid kinases are disrupted in essentially all cancer types. Thus, the study of the phosphoproteome stands to provide unique biological information on signalling pathway activity and on kinase network circuitry that is not captured by genetic or transcriptomic technologies. Here, we discuss the methods and tools used in phosphopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…Proteomic approaches like Redox Proteomics specifically identify proteins that undergo oxidative modifications, providing insights into cancer pathology [ 80 ]. Phosphoproteomics techniques identify oxidative stress-induced phosphorylation changes, crucial in oncogenic signaling pathways [ 81 ]. Metabolomic techniques such as targeted Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) are used for the quantification of specific metabolites like glutathione, directly involved in redox homeostasis [ 82 ].…”
Section: Methods For Oxidative Stress Profiling In Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic approaches like Redox Proteomics specifically identify proteins that undergo oxidative modifications, providing insights into cancer pathology [ 80 ]. Phosphoproteomics techniques identify oxidative stress-induced phosphorylation changes, crucial in oncogenic signaling pathways [ 81 ]. Metabolomic techniques such as targeted Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) are used for the quantification of specific metabolites like glutathione, directly involved in redox homeostasis [ 82 ].…”
Section: Methods For Oxidative Stress Profiling In Oncologymentioning
confidence: 99%
“… Redox Proteomics [ 80 ] Phosphoproteomics Identification of oxidative stress-induced phosphorylation changes. [ 81 ] Metabolomic Techniques Quantification of specific metabolites like glutathione. Targeted LC-MS/MS, Untargeted Metabolomics [ 82 ] [ 83 ]; Imaging Techniques In vivo visualization and real-time monitoring of ROS levels.…”
Section: Methods For Oxidative Stress Profiling In Oncologymentioning
confidence: 99%
“…1A). The phosphopeptides from the embryos were enriched and analyzed with protein mass spectrometry using data-independent acquisition with MS/MS (Gerritsen & White, 2021; Higgins et al, 2023). In total 23,141 unique phosphopeptides were detected (Supplemental Table 1) and the quantities of 2033 phosphopeptides were significantly altered between treatments (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One advantage of proteomics and phosphoproteomics is the ability to provide a direct assessment of the tumor phenotype, rather than using genomic or transcriptomic biomarkers as surrogates to predict drug vulnerabilities [ 93 , 94 ]. Proteomic approaches can be used to detect non-genomic events, including epigenetic changes or influences from the TME, and some preclinical studies have already demonstrated that these approaches may be more reliable predictors of clinical response to treatment than alternative methods [ 94 , 95 , 96 ]. However, the clinical utility of proteomic markers depends on further retrospective analysis of clinical data to refine hypotheses and the success of their validation through prospective clinical trials [ 96 ].…”
Section: Future Directions For Molecular Profiling Of Patients With C...mentioning
confidence: 99%